Carbocisteine Improves Histone Deacetylase 2 Deacetylation Activity via Regulating Sumoylation of Histone Deacetylase 2 in Human Tracheobronchial Epithelial Cells - Song, Yun; Chi, Dan-Yi; Yu, Ping; Lu, Juan-Juan; Xu, Jian-Rong; Tan, Pan-Pan; Wang, Bin; Cui, Yong-Yao; Chen, Hong-Zhuan (Frontiers in Pharmacology, 2019)
Histone deacetylase (HDAC) 2 plays a vital role in modifying histones to mediate inflammatory responses, while HDAC2 itself is commonly regulated by post-translational modifications. Small ubiquitin-related modifier (SUMO), as an important PTM factor, is involved in the regulation of multiple protein functions. Our previous studies have shown that carbocisteine (S-CMC) reversed cigarette smoke extract (CSE)-induced down-regulation of HDAC2 expression/activity in a thiol/GSH-dependent manner and enhanced sensitivity of steroid therapy. However, the mechanism by which S-CMC regulates HDAC2 is worth further exploring. Our study aimed to investigate the relationships between HDAC2 sumoylation and its deacetylase activity under oxidative stress and the molecular mechanism of S-CMC to regulate HDAC2 activity that mediates inflammatory responses in human bronchial epithelial cells. We found that modification of HDAC2 by SUMO1 and SUMO2/3 occurred in 16HBE cells under physiological conditions, and CSE induced SUMO1 modification of HDAC2 in a dose and time-dependent manner. K462 and K51 of HDAC2 were the two major modification sites of SUMO1, and the K51 site mediated deacetylation activity and function of HDAC2 on histone H4 that regulates IL-8 secretion. S-CMC inhibited CSE-induced SUMO1 modification of HDAC2 in the presence of thiol/GSH, increased HDAC activity, and decreased IL-8 expression. Our study may provide novel mechanistic explanation of S-CMC to ameliorate steroid sensitivity treatment in chronic obstructive pulmonary disease.